Customer Preference Factors Affecting e-Groceries Purchase Intention in Indonesia - Yamanie, Aiman; Simangunsong, Elliot (Lembaga Penelitian Publikasi dan Pengabdian Masyarakat LSPR, 2024)
Due to the 2020 COVID-19 pandemic, social distance restrictions, self-quarantines, and isolations all over the world made it impossible for brick-and-mortar stores to stay open. Merchants had to focus on the online ordering to boost sales and ease financial stress as they lost billions of dollars in sales and saw unemployment in the service sector rise. Because of these unusual circumstances, the online grocery ordering system, which lets businesses talk to their prospects and customers online, has become a necessity. Even though retail owners still face problems like losing a lot of money every year and being limited in how far away they can be from their customers, online ordering has protected their business. The App User Interface has an impact on Logistic Service Quality by enabling customers to select a delivery mode seamlessly. Product information, including price, distance, and delivery method, also affects the quality of logistic services. Furthermore, it is found that logistic service quality influences the perceived convenience of online shopping and that the perceived convenience of online shopping influences purchase intention.